Health service by adolescents perspective in Magelang - ., Rohmayanti; Qurrachman, Irwan Taufiq; Nisman, Wenny Artanty (International Journal of Research in Medical Sciences, 2017)
Background: Teenagers are very vulnerable to various threats risks, especially sexual and reproductive health. The government has held an Adolescent Friendly Health Services (AFHS). Carried out in health centers to address adolescent health issues, but have not accommodate the interests of teenagers. Methods: This study was qualitative research using phenomenology approach. Participants were adolescents aged 10-19 years who have received health care services adolescents and health workers selected by purposive sampling. The collection of data using focus group discussions, observation and interview guideline. Analysis of data using the stage of Colaizzi. Results: There is 3 group were involved in this study. Based on data analyses, the results found three themes related to the perception of adolescents based on the type of health services in the AFHS. The themes were positive response, negative response, adolescents expectation. Conclusions: Adolescents have their own perception of the types of services provided and the expectations of the type of service in the future. The government by public health can added the type of service, there is counseling by utilizing adolescent as counselors and using social media to support communication and information on the teenagers. Health workers are expected to raise awareness and show better attitude in adolescents.